Kesan penggunaan modul pengajaran berasaskan masalah terhadap pencapaian dan motivasi pelajar bagi tajuk pengaratan kimia tingkatan lima (IR) - Zikri Awang (2009)
The aim of this study is to compare the problem-based learning (PBL) with conventional learning (CL) by looking at the impact on student motivation and achievement. By using Quasi-experimental method, research were carried on high performance and low performance of form five students from one of the school (n=60). Sampling was collected based on form 4 final exams by using a Quota Sampling method. One education of PBL module were developed based on a short term module by using Dick and Carey specification model with a guiding from Temasek Polytechnics Singapore. The data was collected in the form of response to MSLQ motivational test and achievement test. ANOVA was used to analyse mean score for each performance tests and motivational MSLQ tests from experiment group and control group, Whilst paired sample t-test was used to analyse the ratio increment between pre and post test. The result showed that high performance students from PBL significantly had the best achievement. Meanwhile the achievement increment of students from PBL's low performance group was almost similar to CL's high performance group. The study revealed that PBL should be used as a teaching approach in teaching and learning process to enhance the student motivation and improve the student achievements.